Do we really know that U.S. monetary policy was destabilizing in the 1970s? - Qazi Haque; Nicolas Groshenny; Mark Weder (Bank of Finland, 2019)
The paper re-examines whether the Federal Reserve's monetary policy was a source of instability during the Great Inflation by estimating a sticky-price model with positive trend inflation, commodity price shocks and sluggish real wages. Our estimation provides empirical evidence for substantial wage-rigidity and finds that the Federal Reserve responded aggressively to inflation but negligibly to the output gap. In the presence of non-trivial real imperfections and well-identified commodity price-shocks, U.S. data prefers a determinate version of the New Keynesian model: monetary policy-induced indeterminacy and sunspots were not causes of macroeconomic instability during the pre-Volcker era.
URN:NBN:fi:bof-201909111454
Keywords: E32; E52; E58; 330